The larger bronchi in cryptogenic fibrosing alveolitis: a morphometric study - Edwards, CW (1982)
In a morphometric study of the main, lobar, and segmental bronchi of the left lung in nine cases of cryptogenic fibrosing alveolitis the quantity of gland was found to be significantly greater than in a group of normal controls, and similar to that of a group of patients with chronic bronchitis. The quantity of muscle was also increased, amounts in the segmental bronchi being higher than in the bronchitic patients. The cause of these changes is uncertain, but they seem likely to be due to proximal extension of repeated and persistent infection of the lung parenchyma.